Preparation method of MOFs (Metal-Organic Frameworks) enhanced bacterial cellulose membrane as well as product and application thereof
By growing the MOFs material FJU-66 in the bacterial cellulose membrane and polymerizing and crosslinking with PDDA and BTCA, the film's shortcomings in ionic conductivity and mechanical strength are solved, and efficient hydroxide conductivity and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411866704.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
AI Technical Summary
The existing bacterial cellulose membranes are not excellent in ionic conductivity, and the uneven distribution of PDDA results in insufficient conductivity of the membrane.
A reinforced bacterial cellulose membrane was formed by growing the metal organic frame (MOFs) material FJU-66 in situ in the bacterial cellulose membrane and polymerizing and crosslinking with PDDA and butane tetracarboxylic acid (BTCA).
The long-range ordered and tight three-dimensional network structure of the film is realized, which improves the conductivity and mechanical strength of the hydroxide, while enhancing the oxidation resistance and thermal stability.
Smart Images

Figure CN119552406A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anion exchange membranes, and in particular relates to a preparation method of a MOFs-enhanced bacterial cellulose membrane and a product and application thereof. Background Art
[0002] Bacterial cellulose (BC) is produced by Xylobacterium xylosus, one of the most famous acetic acid bacteria, and consists of ultrafine fibers with a diameter of 3-4 nm and organized into bundles of 40-60 nm thickness, which accumulate to form membranes. These nanofibers are intricately intertwined to form a dense, ultrafine network structure with high specific surface area and complex microporous structure. In addition, unlike plant-derived cellulose, BC lacks lignin, hemicellulose and pectin. Therefore, it exhibits relatively high crystallinity and high hydroxyl content, resulting in excellent mechanical strength and hydrophilicity. However, due to the lack of conductive groups, the nanofibrous structure of BC membranes is not excellent in ionic conductivity, so chemical modification is required. In our previous work, we adopted PDDA as a conductive component to modify the BC substrate, thereby improving the hydroxide conductivity of the membrane. The cationic groups of PDDA are evenly distributed along the main chain, and the adjacent quaternary ammonium groups are about 0.8 nm apart. The hydrogen bond distance between water molecules is about 0.17 nm, while the covalent bond length of -OH in water molecules is about 0.1 nm. Therefore, the uniform distribution of positive charges in PDDA facilitates the OH - The ions are efficiently transported via the Grotthuss mechanism and the surface transport mechanism is enhanced. However, the PDDA inside the membrane still suffers from poor retention and uneven distribution.
[0003] Metal-organic frameworks (MOFs) have higher theoretical specific capacitance, excellent porosity, and size selectivity, and have been widely studied in catalysis and conductivity. Incorporating MOFs into ion exchange membranes has several advantages: 1) forming constrained continuous ion transport channels, 2) establishing internal interactions through adsorption and plate-cage mechanisms to enhance the encapsulation of ion conductors, and 3) micro-nano regulation to improve mechanical properties. Controlling the size of MOF within the BC membrane and achieving uniform distribution is a key challenge in the application process. The pores formed between the interwoven nanoscale BC fibers provide an ideal environment for the in situ growth of nanoscale MOF materials, providing a solution to the challenges of size regulation and uniform growth. Although MOF materials effectively optimize the internal structure of the membrane and establish long and ordered transport channels, they conduct OH - The ion hopping mechanism is still weak. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0005] As one aspect of the present invention, the present invention provides a method for preparing a MOFs-enhanced bacterial cellulose membrane, which comprises the following steps:
[0006] Preparation of BC@FJU-66 / PDDA membrane: copper nitrate, H2NDI, and H3BTC were added to a mixed solution of N, N-dimethylformamide and methanol containing HCl, ultrasonically mixed, bacterial cellulose membrane was added, ultrasonically treated, allowed to stand, reacted at 130-160°C for 2-4 days, washed, dried, placed in a 30-50% diallyldimethylammonium chloride solution, heated to 60-75°C, and an initiator was added to carry out polymerization reaction, washed, and dried to obtain BC@FJU-66-PDDA membrane;
[0007] Preparation of BC@FJU-66 / PDDA-B membrane: The BC@FJU-66-PDDA membrane was immersed in a butanetetracarboxylic acid solution, sodium hypophosphite was added, ultrasonic treatment was performed, drying was performed at 70-90°C, and then baking was performed at 140-160°C. The BC@FJU-66 / PDDA-B membrane was obtained by washing and drying.
[0008] As a preferred solution of the method for preparing the MOFs enhanced bacterial cellulose membrane of the present invention: the mass ratio of copper nitrate, H2NDI and H3BTC is 1:0.9 to 1:1 to 1.2.
[0009] As a preferred scheme of the preparation method of MOFs enhanced bacterial cellulose membrane described in the present invention: in the mixed solution of N,N-dimethylformamide and methanol containing HCl, the volume ratio of HCl, N,N-dimethylformamide and methanol is 1:6-8:2-4; the concentration of HCl in the mixed solution is 0.08-0.12 mol / L.
[0010] As a preferred solution of the method for preparing the MOFs enhanced bacterial cellulose membrane of the present invention: the standing temperature is room temperature and the standing time is 16 to 48 hours.
[0011] As a preferred solution of the method for preparing the MOFs-enhanced bacterial cellulose membrane of the present invention: the initiator includes ammonium persulfate, and the initiator concentration is 0.02-0.1%; the polymerization reaction is carried out under a nitrogen atmosphere.
[0012] As a preferred solution of the method for preparing the MOFs-enhanced bacterial cellulose membrane of the present invention: the mass ratio of BC@FJU-66-PDDA membrane to butane tetracarboxylic acid solution is 0.5-2:100; the concentration of butane tetracarboxylic acid solution is 5-15wt%.
[0013] As a preferred solution of the method for preparing the MOFs-enhanced bacterial cellulose membrane of the present invention: the molar ratio of butanetetracarboxylic acid to sodium hypophosphite is 1:0.3-0.5.
[0014] As a preferred solution of the method for preparing the MOFs enhanced bacterial cellulose membrane of the present invention: baking at 140-160° C. is baking at 150° C. for 15-20 min.
[0015] Beneficial effects of the present invention: The present invention grows MOFs materials in cellulose membranes by combining in-situ growth, polymerization and chemical crosslinking methods, and then synthesizes a series of alkaline anion exchange membranes based on bacterial cellulose (BC) after modification with different concentrations of poly (diallyldimethylammonium chloride) (PDDA) and different concentrations of 1,2,3,4-butanetetracarboxylic acid (BTCA). With the mutual assistance of MOFs, PDDA and BTCA, the membrane can easily construct a long-range ordered and tight three-dimensional network to overcome the disadvantage of excessive pores in the BC membrane. It was confirmed by XRD and FTIR that MOFs materials and PDDA can be firmly clamped into the network, and stability measurements such as thermogravimetric analysis, mechanical properties and antioxidant properties were carried out. The results show that the prepared membrane has good durability under various extreme conditions. Compared with the uncrosslinked membrane, the crosslinked membrane has a relatively low swelling rate and water absorption rate, but the hydroxide conductivity is much higher (BC@FJU-66 / PDDA-B 10 The conductivity is 162.2mS cm -1 At 80°C, the mechanical strength is as high as 80.2MPa. This is attributed to the ability to conduct OH after crosslinking. - The carrier becomes more evenly distributed and has a more compact micro-gap structure. At the same time, it has good antioxidant properties, and the mass remains at about 88% after being immersed in Fenton's reagent at 25°C for 240h. In addition, the prepared cross-linked membrane is assembled into a flexible zinc-air battery (F-ZAB), which can obtain 282.4mW cm- 2 Excellent power density. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:
[0017] Figure 1 is the water absorption and swelling rate of the cross-linked membrane.
[0018] Figure 2 The conductivity variation curves of uncross-linked membrane and cross-linked membrane with temperature and the activation energy of uncross-linked membrane and cross-linked membrane.
[0019] Figure 3 is the stress-strain curve.
[0020] Figure 4 For infrared curve and XRD curve.
[0021] Figure 5 For water contact angle test.
[0022] Figure 6 AFM image.
[0023] Figure 7 TG and DTG curves.
[0024] Figure 8 for oxidation stability and single cell performance. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0026] Embodiment 1:
[0027] Experimental materials and methods: Bacterial cellulose membrane (BC membrane) was purchased from Shanghai Jianglai Biotechnology Co., Ltd. (thickness about 0.05 mm), diallyldimethylammonium chloride (DDA) (60 wt.% aqueous solution), ammonium persulfate, hydrochloric acid, sodium hydroxide, butanetetracarboxylic acid (BTCA) aqueous solution (98%), sodium hypophosphite (NaH2PO2), copper nitrate trihydrate (Cu(NO3)2·3H2O), terephthalic acid (H3BTC), N,N-dimethylformamide (DMF), MeOH methanol was purchased from Sinopharm Chemical Reagent Co., Ltd., and H2NDI was prepared with reference to "Synthesis, Structure and Performance Study of Microporous Metal-Naphthalimide Dipyrazole Framework".
[0028] BC@FJU-66 / PDDA XPreparation of membrane: 0.726g Cu(NO3)2·3H2O, 0.681g H2NDI (2,7-(3,5-dimethyl-1H-pyrazole)-1,4,5,8-tetracarboxylic acid diimide) and 0.75g H3BTC were added to a mixture of DMF / MeOH (120mL / 30mL) containing HCl (15mL, 1mol / L) and ultrasonically mixed for 1h. The BC membrane was then placed in the solution, ultrasonically treated for another 1h, and allowed to stand for 24h. Subsequently, the obtained membrane was placed in a reactor at 150°C for 3 days. The treated membrane was washed with deionized water to remove the MOF on the membrane surface and then dried. Subsequently, the obtained membrane was placed in 100mL of DDA monomer solution with a concentration of 30%, 40% or 50% for 24h. The solution containing the membrane was then transferred to a three-necked flask with a nitrogen feed device. After heating to 70 °C, 0.05 g of ammonium persulfate was added to initiate the polymerization reaction. The polymerization lasted for 1 hour under a nitrogen atmosphere, and then the BC membrane was removed. The unfixed poly(diallyldimethylammonium chloride) PDDA on the membrane surface was thoroughly washed with deionized water (DI). Finally, BC@FJU-66-PDDA was obtained by natural drying. X Films, where X represents different concentrations of DDA solution.
[0029] BC@FJU-66 / PDDA-B X Membrane preparation: BC@FJU-66 / PDDA X The membrane (1 g) was immersed in 100 mL of 10 wt% BTCA aqueous solution. Sodium hypophosphite was used as a catalyst for the esterification reaction, and BTCA: hypophosphorous acid was added to the solution at a molar ratio of 1:0.5. To ensure complete contact between the cellulose matrix and BTCA, ultrasonic treatment was performed for 1 hour. The membrane was dried at 90 °C for 15 minutes and then baked at 150 °C for 15 minutes. The membrane was thoroughly washed with deionized water to remove unreacted and unfixed BTCA on the surface, and then dried naturally to obtain BC@FJU-66 / PDDA-B X Film (thickness about 0.15mm).
[0030] Chemical and structural characteristics:
[0031] Measurement of ion exchange capacity (IEC), water absorption (WU) and swelling ratio (SR):
[0032] OH - The film samples were dried at 60°C for 24 hours to obtain the weight of the dry film (m d , g). The membrane was immersed in 50 mL of hydrochloric acid solution (0.05 M) at 60 ° C for 48 h to make all the OH - The ions are all H +Completely neutralized. At the end of the experiment, the hydrochloric acid solution was titrated with 0.05M sodium hydroxide solution using phenolphthalein as an indicator. At the same time, the volume of sodium hydroxide solution consumed (V2) was recorded. IEC was calculated using the titration method:
[0033]
[0034] Wherein, C1(M) and V1(mL) are the concentration and volume of hydrochloric acid solution, respectively, and C2(M) is the concentration of sodium hydroxide solution.
[0035]
[0036]
[0037] Fourier Transform Infrared Spectroscopy (FT-IR) and Atomic Force Microscopy (AFM):
[0038] The chemical composition of the membrane was analyzed by Fourier transform infrared spectrometer. The bacterial cellulose-based membrane was tested by attenuated total reflection method. The scanning range was 400-4000cm -1 The hydrophobicity / hydrophilicity of the sample surfaces was determined by atomic force microscopy (AFM; Digital Instruments, Veeco). The measurements were performed at a scan size of 11 mm.
[0039] XRD test:
[0040] By X-ray diffraction (XRD): The measurements were carried out in continuous scan mode at 40 kV and 40 mA using a diffraction angle (2θ) between 5° and 60°.
[0041] Water contact angle:
[0042] After the sample was fully dried, the macroscopic hydrophilicity of the membrane surface was measured using a water contact angle meter. The membrane was fixed and tightened with a sample clamp and placed on the test bench. The micro-injection device controlled the water droplet to 2μL, and the sample bench was raised to receive the liquid. The test picture was recorded and the water contact angle was measured.
[0043] Thermal stability and mechanical properties:
[0044] The thermal decomposition of the samples was studied using a STA 449C3 / G thermogravimetric analyzer at a heating rate of 10 °C per minute under N2 atmosphere. Before testing, the AEM was kept dry.
[0045] The mechanical properties of the membrane, including tensile strength and elongation at break, were evaluated at room temperature using a universal material testing machine. The membrane was cut into 1×4 cm pieces and stretched using a 500N sensor at a speed of 5 mm / min. The average value was calculated after several measurements.
[0046] Hydroxide conductivity and chemical stability:
[0047] The OH content of the membrane was measured by electrochemical impedance spectroscopy using an electrochemical workstation. - Conductivity, frequency range is 1MHz~1Hz, amplitude is 100mV. Humidity and temperature are controlled by constant temperature and humidity test chamber. Before testing, the membranes are treated with ion exchange, then cut into 1×1cm size and soaked in deionized water for 24h to ensure the membrane is fully expanded. Its conductivity is:
[0048]
[0049] Where d (cm) is the effective distance between the two reference electrodes, R (Q) and A (cm -2 ) are the resistance and cross-sectional area of the tested AEM samples, respectively.
[0050] The oxidation stability of the sample was tested by measuring the change in mass before and after. The sample was placed in a Fenton reagent solution (25°C) for 240 hours, and the absolute weight of the sample was measured after a certain period of time.
[0051] Single battery performance:
[0052] A membrane electrode assembly was prepared using bacterial cellulose-based anion exchange membrane for single cell performance testing. 2.5 mg Pt, 2.5 mg ruthenium oxide (RuO2) 5% Nafion solution 16 uL and 2 mL ethanol were mixed, and then the mixed solution was ultrasonically treated for 1 h to obtain a catalyst slurry. Subsequently, the catalyst ink was evenly sprayed onto carbon paper on a heating table at 95 ° C, and the catalyst loading was 0.5 mg cm -2 The membrane sample was sandwiched between a Zn plate and carbon paper, and two copper meshes were used as leads to prepare a membrane electrode assembly.
[0053] Water absorption, dimensional stability, ion exchange capacity and OH - Conductivity:
[0054] Water is beneficial to OH -The rapid migration of PDDA enhances the ionic conductivity of the membrane. The data of WU and SR of the uncrosslinked membrane measured at room temperature are shown in Table 1. The results show that all membranes have high water absorption because both bacterial cellulose and PDDA have hydrophilic groups. The water absorption of BC membrane is 100.3%, and the water absorption of BC@FJU-66 membrane is slightly lower than that of BC membrane, because MOFs particles fill part of the pores. However, with the increase of DDA monomer concentration, the water absorption of the composite membrane also shows an upward trend. This is because PDDA fills the pores between bacterial cellulose. The quaternary ammonium group in PDDA is a hydrophilic group. After absorbing water, PDDA further expands the pores of bacterial cellulose, allowing it to accommodate more water. The results show that the volume swelling rate of the membrane is not much different from that of the BC membrane, indicating that the membrane is anisotropic and the size of the membrane does not change at a high water content. Because bacterial cellulose has high crystallinity and high porosity, the structure will not be destroyed when the volume swelling rate of the membrane is relatively high. Figure 1 is the water absorption and swelling rate of the cross-linked membrane. Figure 1 As shown, the water absorption of the cross-linked film reached a minimum value of 88.3% and a minimum swelling ratio of 17.9%, indicating that the dimensional stability of the film was further enhanced after cross-linking.
[0055] OH - Ion exchange capacity (IEC OH - ) determines the conductivity of the ion exchange membrane. Table 1 shows the IEC of BC membrane and composite membrane. OH - The more quaternary ammonium groups there are in the membrane, the more OH - The higher the content, the higher the IEC OH - There is no exchangeable OH in the BC membrane. - The group whose IEC OH - The value is 0.07mequiv·g -1 After in-situ growth of MOFs materials and in-situ polymerization of DDA, IEC OH - Significantly increased, including BC@FJU-66 / PDDA 50 IEC OH - Reach 1.80mequiv·g -1 . High IEC of composite membrane OH - High OH - After BTCA cross-linking, BC@FJU-66 / PDDA-B 10The IEC of the membrane is 1.74, and the uniform distribution of conductive units and the presence of more nanoscale channels are the main reasons for this enhancement. - Transfer groups, enhance the separation of hydrophilic and hydrophobic phases, establish tighter ion transport channels to construct long-distance ordered ion conduction, and improve the selective permeability of the membrane.
[0056] Table 1 Water absorption, swelling rate, ion exchange capacity, OH - Conductivity and strength
[0057]
[0058] OH - Electrical conductivity is one of the main parameters for evaluating the performance of AEMs. As shown in Table 1, at room temperature, OH - The conductivity increases with the increase of DDA monomer concentration, which is due to the increase of ion transport carriers in the membrane. - The conductivity is only 2.7mS·cm -1 The introduction of MOFs makes the polymerization and distribution of PDDA in the membrane more uniform. 40 The conductivity reaches 57.1mS·cm -1 , while BC@FJU-66 / PDDA 50 The conductivity dropped to 45.7 mS·cm -1 This is because the excessively high DDA concentration causes a sudden polymerization during polymerization, which results in uneven distribution of ammonium groups in the membrane, which in turn causes intermittent transmission channels and OH - Therefore, in comprehensive comparison, BC@FJU-66 / PDDA 40 The conductivity performance is the best.
[0059] In addition, Figure 2 The OH of BC basement membrane was discussed in - The relationship between conductivity and temperature is shown in the Arrhenius plot. Figure 2 a), c) the conductivity curves of the uncrosslinked membrane and the crosslinked membrane with temperature; b), d) the activation energy of the uncrosslinked membrane and the crosslinked membrane, such as Figure 2 As shown in (a), OH - The conductivity is positively correlated with temperature. The higher the temperature, the greater the conductivity. 40 At 80℃, it reaches 126.7mS·cm -1 , which is due to the fact that the temperature increases and accelerates the migration of ions. Figure 2 The slopes of the curves in (b) are calculated to show that BC, BC@FJU-66, and BC@FJU-66 / PDDA30 , BC@FJU-66 / PDDA 40 and BC@FJU-66 / PDDA 50 The activation energies are 25.43 kJ·mol -1 、23.11kJ·mol -1 、19.21kJ·mol -1 、13.88kJ·mol -1 and 17.79 kJ·mol -1 , BC@FJU-66 / PDDA 40 The activation energy of the membrane is minimal, which means that the energy required to transport ions is minimal. A large number of ion transport sites reduces the OH - Energy barrier for transmission. Figure 2 As shown in (c), after cross-linking with different concentrations of BTCA, BC@FJU-66 / PDDA-B 10 The membrane has the highest conductivity of 162.2mS·cm -1 At 80°C, it is shown that the appropriate concentration of cross-linking agent promotes the conductivity of the membrane, and the microphase structure of the membrane is more compact and ordered.
[0060] Analysis of mechanical properties of membrane:
[0061] AEMs need to have good mechanical strength to meet practical applications. The strength of the prepared uncrosslinked BC-based membranes is shown in Table 1. The results show that the prepared membranes have satisfactory mechanical strength. The mechanical strength of the BC membrane is 11.1 MPa, and the strength of the membrane has been significantly improved. After the introduction of MOFs and PDDA, because they fill the larger micropores of BC and alleviate the weak points in the membrane, BC@FJU-66 / PDDA 40 The membrane can reach 22.8MPa. However, when the monomer concentration reaches 50%, the mechanical strength tends to decrease. Since DDA polymerization is a free radical polymerization process, the increase in monomer concentration increases the collision rate of free radicals. This leads to the termination of the chain growth reaction, making it challenging to obtain PDDA macromolecules with a high degree of polymerization and resulting in uneven degree of polymerization of the macromolecular chains. This ultimately leads to the formation of more "weak areas" in the membrane, causing local stress concentration. In addition, the shortening of the PDDA molecular chain reduces its ability to interpenetrate and entangle with the BC macromolecular chain, weakens the intermolecular force and has a negative impact on the mechanical properties of the material. To improve this situation, chemical crosslinking was performed with different concentrations of BTCA ( Figure 3 ), appropriate concentration can improve the tensile strength of the film. Figure 3 is the stress-strain curve of the membrane, such as Figure 3 As shown, BC@FJU-66 / PDDA-B 10The membrane exhibited great mechanical strength of 80.1MPa and elongation at break of 9.2%. The cross-linking of BTCA occurs under high temperature conditions, and the active hydroxyl group is connected to the glucose residue C6, which increases the possibility of cross-linking reaction compared to the mild acetal reaction of GA. In addition, in the BTCA molecular structure, in addition to the 1, 2 carboxyl groups or 3, 4 carboxyl groups, the 2, 3 carbons that may be released after BTCA reacts with cellulose can also undergo catalytic anhydride reactions, thereby enhancing the aggregation strength between molecular chains. Excessive concentration may greatly limit the fluidity of cellulose molecules, resulting in a decrease in tensile ductility on the one hand, and on the other hand, the residual substance molecules may exhibit a plasticizing effect, resulting in a decrease in tensile strength and tensile modulus.
[0062] FTIR analysis and XRD analysis of membrane:
[0063] Infrared spectra of BC membrane and composite membrane are as follows: Figure 4 a. All membranes have a peak at 3347 cm -1 The peak at is caused by the stretching vibration of hydroxyl groups in bacterial cellulose. In addition, BC / PDDA 40 Membrane at 3347cm -1 The peak area at BC / PDDA is larger than that of other membranes, further indicating that 40 The membrane has the maximum water absorption rate at 2095cm -1 The peak at 1058 cm is attributed to the stretching vibration of CH. -1 and 1115cm -1 The peaks at 600-1300 cm-1 are caused by the asymmetric stretching vibration of the COC of the pyranose ring in bacterial cellulose. -1 The region of 1650cm2 did not change significantly, indicating that the in-situ growth of MOFs materials and the polymerization process of PDDA in the membrane were not damaged. In addition, all sample membranes except BC membrane showed a 1650cm2 peak caused by CN bending vibration. -1 A significant peak near 1240 cm -1 A weak peak is seen near the DDA. In addition, with the increase of DDA concentration, the CN peak and OH peak gradually increase. This shows that DDA is successfully polymerized and retained in the bacterial cellulose membrane. The intensity of the absorption peak increases with the increase of DDA monomer concentration, which is due to the increase of polymerization degree and the increase of PDDA retained in the membrane.
[0064] from Figure 4 b It can be seen that the characteristic diffraction peaks at about 14.8°, 16.8°, and 22.5° in the original BC film correspond to (1 10), (110), and (200) crystal planes. According to the Bragg law, the interplanar spacing of each crystal plane was calculated to be 0.597nm, 0.527nm, and 0.395nm, respectively, indicating that the intracrystalline region of the pure BC film is a typical cellulose I crystal. The three typical peaks also exist in the corresponding spectra of other BC-based films, indicating that the in-situ polymerization and cross-linking treatment cannot change the basic properties of its crystal structure. In addition, BC@FJU-66 / PDDA 40 and BC@FJU-66 / PDDA-B 10 Characteristic peaks appeared in other locations of the membrane, indicating that MOFs were successfully introduced into the membrane.
[0065] Water contact angle analysis of membranes: The water contact angle test is used to analyze the macroscopic hydrophilicity of the membrane surface to water. The more hydrophilic the surface is, the more conducive it is to the penetration of water molecules, which in turn helps the transmission of ions. Figure 5 for a)BC@FJU-66 / PDDA X (X = 30, 40, 50) Water contact angle of the film; b) C@FJU-66 / PDDA-B X (X=5, 10, 15) water contact angle of the film, Figure 5 a is the water contact angle picture of the prepared membrane. It can be clearly seen that the water contact angles of all membranes are less than 90°, indicating that each membrane has hydrophilic properties, which provides a positive influence on high conductivity. On the one hand, this is because bacterial cellulose is rich in a large number of hydrophilic hydroxyl groups and has a three-dimensional pore structure. On the other hand, the quaternary ammonium group of PDDA is also a hydrophilic substance. The two complement each other. With the increase of DDA polymerization concentration, the water contact angle of the uncrosslinked membrane tends to increase, and BC@FJU-66-PDDA 50 The maximum water contact angle is 70°. This is because the pores of the membrane are filled. Compared with the porous original membrane, water molecules encounter certain resistance when entering the membrane. Figure 5 b The water contact angle of the cross-linked membrane is positively correlated with the increase of the cross-linking agent concentration. This is because the pores on the membrane surface are filled with MOFs materials and macromolecular chains PDDA on the one hand; on the other hand, the three-dimensional pores of the membrane are further compressed with the increase of the cross-linking degree, which leads to the BC@FJU-66-PDDA-B 15 The membrane has a maximum water contact of 75°.
[0066] Surface image analysis of membranes:
[0067] Figure 6 for a)BC / PDDA 40 AFM image of the membrane; b) BC@FJU-66 / PDDA 40 AFM image of the membrane; c) BC@FJU-66 / PDDA-B 10AFM images of the membranes. With the addition of PDDA, BC / PDDA 40 The roughness of the film is reduced to 18.9nm ( Figure 6 a), because PDDA fills the pores and makes the surface smooth. Pure BC and BC / PDDA 40 The films were all highly hydrophilic, indicating that the increase in surface roughness further enhanced the hydrophilicity, which is consistent with earlier water contact angle measurements. In general, the hydrophilicity of a film is directly related to its surface roughness and the nature of the surface chemical groups. Increased roughness tends to enhance the hydrophilicity of a hydrophilic surface and increase the hydrophobicity of a hydrophobic surface. After adding a MOF with hydrophobic properties, BC@FJU-66 / PDDA 40 ( Figure 6 b) The roughness of the membrane (Rq = 23.0 nm) increased. An increase in roughness tends to amplify the hydrophilicity of hydrophilic surfaces and enhance the hydrophobic surface. The highest roughness (Rq = 28.3 nm) was observed in the cross-linked membrane. Figure 6 c), where the cross-linking reaction blocks the hydrophilic -OH groups on the surface, indicating this change in film roughness consistent with the water contact angle measurements of the above films.
[0068] Thermal stability analysis of membranes:
[0069] The thermal stability of the membrane is an important measurement indicator of AEMs in practical applications. Good thermal stability is an important basis for AEMs to operate stably and for a long time at high temperatures. Figure 7 ) are the TG and DTG curves of the membrane. From the curve of the BC membrane, it can be seen that Figure 7 (a) The thermal degradation of BC membrane can be divided into two stages. The first stage is from 30℃ to 150℃. This stage is mainly due to the evaporation of water in the membrane, and the mass loss is about 3.5%. The second stage is from 250℃ to 400℃. This stage is mainly due to the breakage and decomposition of the main chain of bacterial cellulose. BC@FJU-66-PDDA 40 and BC@FJU-66-PDDA-B 10 The degradation of the membrane is mainly divided into three stages. The first stage at 30℃~150℃ is also due to the evaporation of water, and the mass loss is about 6%, which is higher than the loss of BC membrane in this stage. This is because a lot of PDDA is retained in the membrane, which is more likely to absorb moisture in the air; the second stage from 250℃~400℃ is mainly due to the breakage of cellulose chains and the degradation of quaternary ammonium groups in PDDA; the third stage from 400℃~500℃ is attributed to the decomposition of MOFs materials and alkyl chains in PDDA. Figure 7 (b) shows that their maximum decomposition temperatures are 332℃, 290℃ and 300℃, respectively. 40The maximum degradation temperature of the membrane is advanced because the decomposition temperature of the quaternary ammonium group is earlier than the degradation temperature of cellulose. In addition, the introduction of PDDA weakens the hydrogen bonds between cellulose molecular chains, which makes the degradation temperature of the cellulose main chain also advanced. However, after esterification with BTCA, new chemical bonds are formed, thereby enhancing the resistance to thermal decomposition of cellulose chains. 10 The membrane degradation temperature is extended to 300°C. The prepared composite membrane has good thermal stability within 200°C, meeting the needs of anion exchange membranes in practical applications.
[0070] Oxidation resistance of membrane:
[0071] In the actual application process, there will be some active free radicals attacking the membrane material. Excellent antioxidant properties are an important backing for the membrane in the actual application process. Figure 8 For a) the oxidation stability of the membrane, b) the performance of the single cell, Figure 8 As can be seen from a, BC@FJU-66-PDDA / B 10 The mass retention rate of the membrane in Fenton's reagent (91.5%) is higher than that of the uncrosslinked membrane (86.4%). This is mainly because the ferrous ions in the Fenton's reagent accelerate the decomposition of hydrogen peroxide and produce more OH and HO2 free radicals in the initial reaction stage. 40 Without chemical cross-linking, the internal structure is relatively loose, and a large number of free radicals can easily penetrate the membrane, degrading the macromolecular chains of BC and PDDA from the inside out, resulting in a rapid decrease in mass retention. After cross-linking, the internal structure of the membrane becomes relatively dense, making it difficult for a large number of free radicals generated by the Fenton reagent to penetrate.
[0072] Single battery performance:
[0073] The power generation mechanism of zinc-air battery can be explained by the following electrochemical reaction: Anode: Zn+4OH - →Zn(OH)4 2- +2e - , Zn(OH)4 2- →ZnO+2OH - +H2O; cathode: O2+H2O+4e - →4OH - ; Overall reaction formula: 2Zn+O2→2ZnO. By combining excellent electrochemical performance and adjustable operating conditions with AEMs with high ionic conductivity and excellent mechanical properties, efficient zinc-air batteries can be achieved. During battery operation, hydroxide reacts with zinc at the cathode through the prepared membrane to form zinc oxide, and the 4e generated at the anode - is transported to the external circuit and reaches the cathode. The polarization curve and power density curve are shown in Figure 8As shown in b, BC@FJU-66 / PDDA is used 40 and BC@FJU-66 / PPDA-B 10 The open circuit voltages of the Zn / O2 cell as a separator were 1.40 V and 1.42 V, respectively, indicating excellent airtightness, while the power density was 209.5 mW cm -2 and 282.4 mW cm -2 The peak current density is 360.3 mA cm -2 and 340.6 mA cm -2 , which proves that the F-ZAB membrane prepared in this experiment has good power generation ability at room temperature.
[0074] In summary, the present invention successfully prepared a series of AEMs with bacterial cellulose (BC) membrane as the matrix with high porosity and biocompatibility through simple and efficient in-situ growth, polymerization and cross-linking reactions. MOFs material FJU-66 was used as the filling unit, diallyldimethylammonium chloride (DDA) was used as the ion conductor, and a series of BC-based anion exchange membranes were prepared by encapsulation with different concentrations of BTCA. FTIR and XRD measurements confirmed that MOFs and the conductive unit PDDA have been firmly locked in the three-dimensional network constructed by BC through a variety of combinations such as intermolecular interaction forces and cross-linking. According to the OH - Conductivity study: the cross-linked membrane can reach 162.2 mS cm at 80 °C -1 (BC@FJU-66 / PPDA-B 10 ), thermal stability can reach 443°C, mechanical strength can reach 80MPa, and good antioxidant properties. FT-IR spectroscopy and XRD analysis showed that MOFs and DDA successfully grew and polymerized and were successfully sealed in the pore-rich BC membrane by the cross-linker. Water contact angle analysis showed that the surface of the prepared anion exchange membrane had a hydrophilic property, which was conducive to the transmission of ions. In F-ZAB, the overall performance of the cross-linked membrane is very excellent, with a high electrochemical value: 1.4V and high power density. In short, the bacterial cellulose-based anion exchange membrane with good comprehensive performance prepared by the present invention is expected to be used in practical applications.
[0075] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a MOFs-enhanced bacterial cellulose membrane, characterized in that: It consists of the following steps: Preparation of BC@FJU-66 / PDDA membrane: copper nitrate, H2NDI, and H3BTC were added to a mixed solution of N, N-dimethylformamide and methanol containing HCl, ultrasonically mixed, bacterial cellulose membrane was added, ultrasonically treated, allowed to stand, reacted at 130-160°C for 2-4 days, washed, dried, placed in a 30-50% diallyldimethylammonium chloride solution, heated to 60-75°C, and an initiator was added to carry out polymerization reaction, washed, and dried to obtain BC@FJU-66-PDDA membrane; Preparation of BC@FJU-66 / PDDA-B membrane: The BC@FJU-66-PDDA membrane was immersed in a butanetetracarboxylic acid solution, sodium hypophosphite was added, ultrasonic treatment was performed, drying was performed at 70-90°C, and then baking was performed at 140-160°C. The BC@FJU-66 / PDDA-B membrane was obtained by washing and drying.
2. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1, characterized in that: The mass ratio of copper nitrate, H2NDI and H3BTC is 1:0.9~1:1~1.
2.
3. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: In the mixed solution of N,N-dimethylformamide and methanol containing HCI, the volume ratio of HCI, N,N-dimethylformamide and methanol is 1:6-8:2-4; and the concentration of HCI in the mixed solution is 0.08-0.12 mol / L.
4. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: The temperature of the standing is room temperature, and the time is 16 to 48 hours.
5. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: The initiator includes ammonium persulfate, and the concentration of the initiator is 0.02-0.1%; the polymerization reaction is carried out under a nitrogen atmosphere.
6. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: The mass ratio of BC@FJU-66-PDDA membrane to butane tetracarboxylic acid solution is 0.5-2:100; the concentration of butane tetracarboxylic acid solution is 5-15wt%.
7. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: The molar ratio of butanetetracarboxylic acid to sodium hypophosphite is 1:0.3-0.
5.
8. The method for preparing a MOFs-enhanced bacterial cellulose membrane according to claim 1 or 2, characterized in that: Baking at 140-160°C is followed by baking at 150°C for 15-20 minutes.
9. The MOFs enhanced bacterial cellulose membrane prepared by the method for preparing the MOFs enhanced bacterial cellulose membrane according to claim 1.
10. Application of the MOFs-enhanced bacterial cellulose membrane prepared by the method for preparing the MOFs-enhanced bacterial cellulose membrane according to claim 1 in anion exchange membrane and flexible zinc-air battery.
Citation Information
Cited By
Antibacterial polypropylene master batch and preparation method thereof
CN120484386A